Difficulties Encountered by EFL Teachers when Developing Vocabulary. The Case study of First Year at University of Lagouat - BENMESSAOUD, Mourad; NOUIOUA, Amira (University of Ammar Theledji -Laghouat, 2020)
This work is an attempt to investigate the difficulties encountered by teachers when developing vocabulary of English as foreign language (EFL). Following many researches, and experts﮲observations, the difficulties generally refers to lack of specific diagnosing the learners disabilities . Therefore, if the teacher determines the type of weakness among his learners and apply various strategies and techniques , he will invest the time successfully in raising the level of terminology and vocabulary of his learners . To accomplish this study, an interview has been done with teachers of English at University of Lagouat and a questionnaire given to first year EFL students in the department. We find that the students base on the teachers explanation to understand unknown words , which may be difficult for the teacher to develop the students `vocabulary . However, the students find that their own efforts make them acquire and develop their vocabulary better than relying on the teachers `explanation . so this results have confirmed our hypothesis that if the teachers cooperate to develop the level of vocabulary by using different strategies and techniques; they will defeat a lot of difficulties and they help their learner not only to develop their vocabulary but they also make them learn alone and carrying out learning smoothly the other skills